Transforming Marketing and Tourism: Harnessing Virtual Reality for Immersive Consumer Experiences in Switzerland - Andziak, Anita (Global journal of Business and Integral Security, 2024)
The following study investigates the impact of virtual reality on the effectiveness of marketing strategies and tourist experience in the Swiss city of Solothurn. A quantitative analysis was conducted on 427 participants to assess their interaction with virtual reality and its impact on brand loyalty and its role in increasing consumer engagement. The study findings indicate that the use of VR technology significantly increases consumer engagement, notably in the context of tourism marketing. The presentation of interactive virtual tours of historic sites in Solothurn has been observed to stimulate greater interest among visitors. The results of the statistical analyses indicate that many participants consider the VR technology to be innovative and effective in increasing trust and brand loyalty. However, the widespread uptake of VR is limited by barriers such as high equipment costs and fatigue. Future research should focus on examining the long-term impact of VR on consumer behaviour and its potential in different cultural contexts, with the aim of optimising its application in marketing and tourism.